Village Baseline Study: Site Analysis Report for Ekxang village Phonghong district, Vientiane province, Lao PDR - Grant, Angela; Mienmany, Soytavanh; Keophoxay, Anousith; Khodyhotha, Khamphamy; Phonevisay, Silivong; Souvannaxayyavong, Chantha; Toummavong, Phetsamone; Chidvilaphone, Saythong; Khamkhosy, Neeny; Pavelic, Paul; Bouapao, Lilao; Palikone, Thalongsengchanh; et al. (2015)
Data collection for the Village Baseline Study for the Ekxang Climate-Smart Village located in Phonhong District, Vientiane Province, Lao PDR, took place on November 19th - 21st, 2014. Three days of focus group discussions were conducted separately for men and women. Participatory methods were used to gather information on community resources, organizational landscapes, information networks, and the community’s vision for the future. Men and women in Ekxang village had different point of views on their community’s resources. Women were focused more on the conservation and increased forest land as they are responsible for collecting the Non-Timber Forest Product. Men were more interested in the development of agro-forestry. Regarding agriculture, men were focused on rice paddies while the women were more focused on the smaller household vegetable gardens. There were several changes in community resources. Forest and pasture areas were significantly degraded due to urban development, increasing people demands, and expansion of agricultural lands since 1980s. Infrastructures for irrigation were improved 30 years ago to expand the irrigated area but only few households in Ekxang could benefit from it. Villagers experience that soil fertility has declined compared to 25 years ago. There were a number of organizations operating at the village, half of them related to food security, food crisis and natural resource management. However, linkages is not strong the organizations. Farmer-to-farmer, mobile phone and television are main sources of information that support farmers in their decision making. There is a high potential to develop ICT-based technologies in order to support climate-smart farming practices to farmers. From the farmers’ perspective, their Climate-Smart Village should be an agroforestry landscape with smart groundwater use, smart pest management and crop diversification, and smart information services.